Legal regulation of the activities of environmental whistleblowers in international law - Panfilova, Yulia; Mykhailovskyi, Viktor (Український політико-правовий дискурс, 2026)
The article examines the international legal framework environmental whistleblowers, protection as an essential element of ensuring the human right to a safe environment. The relevance of the topic is caused by increasing environmental risks, the complexity of detecting environmental violations, and the critical role of individuals who disclose such misconduct. The study analyzes international standards, particularly the Aarhus Convention and the EU Whistleblower Protection Directive (2019/1937), which establish guarantees for access to information, reporting channels, and protection against retaliation. It is established that whistleblowers play a crucial role in ensuring the enforcement of environmental law, as they are often the first to detect violations posing serious threats to public interests. Particular attention is paid to international legal protection including the lack of a unified definition of whistleblowers, fragmentation of legal regulation, and insufficient effectiveness of protection mechanisms. Despite the introduction of minimum EU standards, gaps in implementation persist, particularly regarding protection against retaliation and reporting systems functional. The article proposes recommendations aimed at improving legal regulation, including the need international standards, strengthening legal guarantees, and enhancing enforcement mechanisms. For Ukraine, the importance of aligning national legislation with European standards, improving reporting procedures, and ensuring effective protection against retaliation is emphasized. Future development should focus on creating a comprehensive and coherent system of international safeguards for environmental whistleblowers.